Satire in the newspaper «Syr boiy» (Herald of Journalism, 2016)
This article discusses the materials published in the regional newspaper «Syr boiy» analyzes used by the authors of various publications means to influence readers. Particular attention is paid to the satirical section, which at different times had different names. The article notes that the publication of this section have contributed to the development of the genreof satire, as well as provided on the impact of readers as a means of education.
Keywords: genres of satire; satirical angle; means of education